A novel application of the lotus petal flap in high-risk perineal urethrostomy: principles and outcomes - Daniel J Reilly; Eric K Sham; Justin BL Chee; Ajay Chauhan (Australasian Journal of Plastic Surgery)
**Introduction**: Perineal urethrostomy is a valuable technique in the management of complex anterior urethral strictures, as well as following penectomy or urethrectomy. Traditional techniques that employ perineal or scrotal skin flaps have documented failure rates of up to 30 per cent. Current techniques for salvage have only modest success, leaving patients few options other than permanent suprapubic catheter or cystectomy and ileal conduit formation.